Usefulness of 3-Dimensional Flexible Endoscopy in Esophageal Endoscopic Submucosal Dissection in an Ex Vivo Animal Model. (3rd November 2019) - Higuchi, Kazutoshi; Kaise, Mitsuru; Noda, Hiroto; Ikeda, Go; Akimoto, Teppei; Yamawaki, Hiroshi; Goto, Osamu; Ueki, Nobue; Futagami, Seiji; Iwakiri, Katsuhiko
Abstract : Background and Aims. Three-dimensional (3D) rigid endoscopy has been clinically introduced in surgical fields to enable safer and more accurate procedures. To explore the feasibility of 3D flexible endoscopy, we conducted a study comparing 2-dimensional (2D) and 3D visions for the performance of esophageal endoscopic submucosal dissection (ESD). Methods. Six endoscopists (3 experts and 3 trainees) performed ESD of target lesions in isolated porcine esophagus using a prototype 3D flexible endoscope under 2D or 3D vision. Study endpoints were procedure time, speed of mucosal incision and submucosal dissection, number of technical adverse events (perforation, muscle layer damage, and sample damage), and degree of sense of security, fatigue, and eye strain. Results. Procedure time and speed of mucosal incision/submucosal dissection were equivalent for 2D and 3D visions in both experts and trainees. The number of technical adverse events using 2D vision (mean [standard deviation], 3.5 [4.09]) tended to be higher than that using 3D vision in trainees (1.33 [2.80]; P = .06 ). In experts, 2D and 3D visions were equivalent. The degree of sense of security using 3D vision (3.67 [0.82]) was significantly higher than that using 2D vision (2.67 [0.52]) in trainees (P = .04 ), but was equivalent in experts. The degree of eye strain using 3D vision (3.00 [0.00]) was significantly higher than that using 2D vision (2.17 [0.41]) in trainees, but was equivalent in experts. Conclusions. 3D vision improves the sense of security during ESD and may reduce technical errors, especially in trainees, indicating the feasibility of a clinical trial of ESD under 3D vision.